1984
DOI: 10.1021/i200024a017
|View full text |Cite
|
Sign up to set email alerts
|

Design of packed, adiabatic absorbers: physical absorption of acid gases in methanol

Abstract: An algorithm was developed to calculate concentration and temperature profiles for an adiabatic, packed absorber. Calculations performed with this algorithm compared favorably wlth data obtained on a pilot scale absorber having a diameter of 0.127 m (5 in.) and packed with 6.2s" (0.25 in.) ceramic Intalox saddles. The data were obtained for absorption of acid gases from a stream produced from cylinder gases and by coal gasification; refrigerated methyl alcohol was the solvent used in the absorber. The systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A comprehensive study of a process for removing acid gases using methanol was recently reported by Kelly et al (1984) (see also Kelly et al, 1981 andKelly, 1981). These acid gases must be removed from the main products in order to increase the energy content as well as to meet environmental standards.…”
Section: The Processmentioning
confidence: 99%
See 4 more Smart Citations
“…A comprehensive study of a process for removing acid gases using methanol was recently reported by Kelly et al (1984) (see also Kelly et al, 1981 andKelly, 1981). These acid gases must be removed from the main products in order to increase the energy content as well as to meet environmental standards.…”
Section: The Processmentioning
confidence: 99%
“…Physical solvents are preferred for bulk removal when all of these factors must be taken into consideration; refrigerated methanol has been found to be a possible alternative to MEA and DEA. A comprehensive study of a process for removing acid gases using methanol was recently reported by Kelly et al (1984) (see also Kelly et al, 1981 andKelly, 1981). A large number of experiments were done on the absorber, using both standard gases (mixtures of nitrogen and carbon dioxide from cylinders) and product gas from a coal gasifier.…”
Section: The Processmentioning
confidence: 99%
See 3 more Smart Citations